2021
DOI: 10.7759/cureus.16078
|View full text |Cite
|
Sign up to set email alerts
|

A Case of COVID-19-Associated Autoimmune Hemolytic Anemia With Hyperferritinemia in an Immunocompetent Host

Abstract: We report an interesting case of a middle-aged gentleman who presented with diabetic ketoacidosis (DKA) and tested polymerase chain reaction (PCR) positive for COVID-19 infection. His hospital stay was complicated by acute kidney injury, hematuria, and normocytic anemia. Initial chest x-ray demonstrated bibasilar opacities. D-dimer and C-reactive protein were elevated. During his hospital stay, his hemoglobin decreased from 13.4 g/dL to 9 g/dL, and further workup demonstrated ferritin of 49,081 ng/mL with lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Autoimmune hemolytic anemia is a rare autoimmune disorder that could occur in association with several autoimmune, malignant, or infectious diseases such as human immunodeficiency virus, mycoplasma, hepatitis B, cytomegalovirus, and parvovirus [3,4]. Association with novel coronavirus is rare [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoimmune hemolytic anemia is a rare autoimmune disorder that could occur in association with several autoimmune, malignant, or infectious diseases such as human immunodeficiency virus, mycoplasma, hepatitis B, cytomegalovirus, and parvovirus [3,4]. Association with novel coronavirus is rare [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Although the primary pathophysiology causing severe disease in COVID-19 remains unclear, prevailing evidence supports an event of acute cytokine storm being associated with disease severity and negative outcome [2]. However, the range of complications is wider and includes amongst other several auto-immune disorders such as autoimmune thrombocytopenia, Guillain-Barré syndrome, and anti-phospholipid syndrome [2,3]. Here we report a case of a young woman with autoimmune hemolytic anemia (AIHA) during COVID-19 infection for the first time in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…Patil et al concluded in a case report research that COVID‐19 infection could result in thromboembolism, coronary artery disease, and AIHA and should be regarded as a probable cause of these uncommon disorders (Patil et al, 2020). AIHA was also identified as a COVID‐19 consequence (Huda et al, 2021). Secondary AIHA caused by COVID‐19 is uncommon, with only a few COVID‐19‐related w‐AIHA instances recorded.…”
Section: Autoimmunity Post‐covid‐19 Infectionmentioning
confidence: 99%
“…3a and b) [74], reticulocytosis (Fig. 3c) [75], unconjugated bilirubinemia, increased serum LDH activity, ferritin, and low haptoglobin were also observed [10,73,74,76]. Moreover, increased D-dimer and C-reactive levels were reported due to hypercoagulability and hyperinflammatory response in most SARS-CoV-2-associated AIHA cases [19,[72][73][74]76].…”
Section: Aiha Diagnosis In the Setting Of Covid-19 Infectionmentioning
confidence: 99%
“…Extended examinations, including chest X-rays, showed bilateral opacities (Fig. 3d) [73,76], while chest computed tomography showed typical COVID-19 infection changes in the lung (Fig. 3c) [74,75].…”
Section: Aiha Diagnosis In the Setting Of Covid-19 Infectionmentioning
confidence: 99%